Subtitusi Tepung Mocaf dan Buah Naga dalam Pembuatan Dadar Gulung - Felix Infan Nandhiwardana; Sugiman Sugiman; Isnanda Putri Nur Istiqomah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the application of mocaf flour as a partial or complete substitute for wheat flour in the preparation of dadar gulung, a traditional Indonesian delicacy. The research is grounded in the potential of mocaf, which is gluten-free, rich in dietary fiber, and supports efforts to diversify food sources based on local commodities. A quantitative experimental method was employed with three flour formulations 50% wheat : 50% mocaf, 25% wheat : 75% mocaf, and 100% mocaf evaluated through organoleptic testing by 25 panelists with varying levels of experience. The assessment parameters included color, aroma, taste, texture, and overall perception. The findings indicate that the formulation containing 100% achieved the highest overall score, followed by the 75% mocaf and 25% wheat blend, while the 50% mocaf and 50% wheat formulation ranked lowest. These results suggest that a dominant proportion of mocaf can maintain the sensory quality of the product, although full substitution requires further optimization to enhance consumer acceptance. This research contributes to the development of healthier innovations in traditional foods, offers a gluten-free alternative for individuals with dietary restrictions, and promotes the sustainable utilization of local resources.